NILAI KEAGAMAAN DALAM NOVEL COGITO ALLAH SUM KARYA LALU MUHAMMAD ZAINUDIN - dede muhtar; Ahmad Arifin; Mohadib (Politeknik Negeri Jakarta, 2026)
Abstract This research focuses on the depiction of religious values ​​in the novel CAS by LM Zainudin. The reason religious values ​​are the focus of this research is because they are the most fundamental social cultural values ​​for community life. The novel CAS contains many religious values ​​that can be useful for society, and the religious values ​​in the novel CAS contain Islamic nuances that are beneficial for readers. The religious values ​​reflected in the novel CAS include 1) religious values ​​towards Allah SWT, 2) religious values ​​towards the Prophet Muhammad (peace be upon him), 3) personal religious values, 4) religious values ​​within the family, and 5) religious values ​​within society. The relationship between the religious values ​​in the novel CAS by LM Zainudin and the reality of contemporary society is that the religious values ​​in the novel CAS are a clear reflection of the current social conditions in society that no longer uphold religion in life. The researcher used a qualitative descriptive research method. The data collection methods used in this study were 1) reading and note-taking, 2) literature review, and 3) analysis. The data analysis method was carried out by 1) reading carefully, 2) finding data and entering it into data cards, and 3) analyzing and interpreting the obtained data in the form of religious values. Keywords: values, religion, sociology, literature